Perancangan Fotografi Pemandian Umbul Dalam Buku Direktori Sebagai Promosi Wisata Kabupaten Boyolali - Auriga Hendrawan; Evelyne Henny Lukitasari; Arif Yulianto (JURNAL KEMADHA, 2022)
AbstractBoyolali is a district in the province of Central Java. Boyolali has attractive tourism potential. Thereare various tourist attractions in Boyolali Regency, including culinary tourism, cultural tourism,and nature tourism, as well as other tours. One of the tourist attractions that have strong potentialis water springs tourism. There are Pengging, Tlatar, Leses, Kendat, Tirto Mulyo, Langse watersprings and others. Water springs tourism is still less well known and accessible to the widercommunity due to the lack of promotional media. The solution is introducing water springs tourismin Boyolali through a directory book that displays photography with explanations. This promotionalmedia is expected to introduce more potential water springs tourism and provide benefits by buildingcommunication and bringing in tourists. The design of a directory book as a promotional media forwater springs in Boyolali was prepared with initial ideas, surveys, design and evaluation methods.The creation of promotional media for the pennant directory book in Boyolali is expectedto increase tourist attraction.Keywords: Design, Photography, Directory Books, Boyolali